DETERMINATION OF VITAMIN A AND VITAMIN C IN CORCHORUS OLITORIUS (BUSH OKRA) USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (FUDMA JOURNAL OF SCIENCES, 2023)
Vitamins A and C are essential to humans as they play important roles in general metabolic processes and maintenance of good health conditions. Their essentiality is based on the fact that they cannot be synthesized by humans but must be consumed from plant based foods. Corchorus olitorius (Jew’s mallow) being a widely cultivated and consumed vegetable either fresh or dried in Nigeria would serve as a reliably cheap and quantitative source of vitamins A and C. It has been used for healing benefits as natural medicinal herb as it has been used to treat and manage many diseases. This study was carried out to determine the vitamins A and C content in the fresh and dried leaf of Corchorus olitorius by using high performance liquid chromatography (HPLC). The fresh sample was found to contain 0.056 mg/ml of vitamin A and 0.108 mg/ml of vitamin C while the dried leaf was found to contain 0.162 mg/ml of vitamin A and 0.211 mg/ml of vitamin C. The result shows that the dried leaf of Corchorus olitorius contains higher concentration of vitamins A and C than the fresh vegetable. This is an advantage especially for people living in the rural areas as it can be dried and stored for future use with the vitamin content still maintained
Keywords: Corchorus olitorius, Green Vegetable, HPLC, Vitamin A, Vitamin C